A Review of Traditional and Emerging Residual Chlorine Quenchers on Disinfection By-Products: Impact and Mechanisms - Xue Li; Zhijing Zhao; Zheng Qu; Xinyu Li; Zengli Zhang; Xiaojun Liang; Jingsi Chen; Jiafu Li (Toxics, 2023)
Disinfection by-products (DBPs) are the most common organic contaminants in tap water and are of wide concern because of their highly developmental toxic, cytotoxic, and carcinogenic properties. Typically, to control the proliferation of pathogenic microorganisms, a certain concentration of residual chlorine is retained in the factory water, which reacts with the natural organic matter and the disinfection by-products that have been formed, thus affecting the determination of DBPs. Therefore, to obtain an accurate concentration, residual chlorine in tap water needs to be quenched prior to treatment. Currently, the most commonly used quenching agents are ascorbic acid, sodium thiosulfate, ammonium chloride, sodium sulfite, and sodium arsenite, but these quenching agents can cause varying degrees of DBPs degradation. Therefore, in recent years, researchers have attempted to find emerging chlorine quenchers. However, no studies have been conducted to systematically review the effects of traditional quenchers and new ones on DBPs, as well as their advantages, disadvantages, and scope of application. For inorganic DBPs (bromate, chlorate, and chlorite), sodium sulfite has been proven to be the ideal chlorine quencher. For organic DBPs, although ascorbic acid caused the degradation of some DBPs, it remains the ideal quenching agent for most known DBPs. Among the studied emerging chlorine quenchers, n-acetylcysteine (NAC), glutathione (GSH), and 1,3,5-trimethoxybenzene are promising for their application as the ideal chlorine quencher of organic DBPs. The dehalogenation of trichloronitromethane, trichloroacetonitrile, trichloroacetamide, and bromochlorophenol by sodium sulfite is caused by nucleophilic substitution reaction. This paper takes the understanding of DBPs and traditional and emerging chlorine quenchers as a starting point to comprehensively summarize their effects on different types of DBPs, and to provide assistance in understanding and selecting the most suitable residual chlorine quenchers during DBPs research.